Sosialisasi dan Pelatihan Pembuatan Pupuk Kompos Menggunakan Limbah Kotoran Ternak - Rusminah Hs; Muh. Sohibul Akbar; Muhammad Haikal Fadillah Firdausi; Wenvy Andani; Farel Harisugama (Universitas Mataram, 2022)
Compost includes organic fertilizers derived from plant residues and animal manure that have undergone a decomposition or weathering process. This service activity aims to provide training and practice in making compost from livestock manure in Ketangan Village, Suela District, East Lombok Regency. The method used is socialization and training at the house of the Head of the Tejong Daya village, Ketangan Village, Suela District, East Lombok Regency. The program of activities carried out includes socialization and training on processing livestock manure into compost. The socialization and training on making compost from livestock manure was carried out for 1 day by giving demonstrations on how to make compost. The process of making compost can be observed directly by the surrounding community. This will increase the knowledge of the people of Ketangan village about making compost. The conclusion of this activity is that the farmers in Tejong Daya Hamlet, Ketangan Village are very enthusiastic about the KKN work program. The results of organic fertilizers obtained are expected to be applied to agricultural land to reduce the use of chemical fertilizers.